2022
DOI: 10.3762/bjoc.18.3
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional thiourea-catalyzed asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins

Abstract: Bifunctional thiourea-catalyzed asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins have been developed to afford chiral dispiro[indene-pyrrolidine-pyrimidine]s. Through this strategy, the target products could be obtained in good to excellent yields with excellent stereoselectivities. In addition, the synthetic utility was verified through a gram-scale synthesis, one-pot three-component reactions and further transformation experiments of the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…1 Related Cinchona and its thio(urea)/squaramide derivative catalysed Michael addition of carbanions to β-nitrostyrenes has seen resurgence of activity. 2 Impressive advances in vinylogous Michael addition and tandem cyclization have also been made via Cinchona -mediated catalysts. 3 The Cinchona based organocatalysts have a wide range of applications in various asymmetric reactions, including aldol, 4 Morita–Baylis–Hillman, 5 Mannich, 6 and dihydroxylation 7 where the quinuclidine portion works as an activator for nucleophiles.…”
mentioning
confidence: 99%
“…1 Related Cinchona and its thio(urea)/squaramide derivative catalysed Michael addition of carbanions to β-nitrostyrenes has seen resurgence of activity. 2 Impressive advances in vinylogous Michael addition and tandem cyclization have also been made via Cinchona -mediated catalysts. 3 The Cinchona based organocatalysts have a wide range of applications in various asymmetric reactions, including aldol, 4 Morita–Baylis–Hillman, 5 Mannich, 6 and dihydroxylation 7 where the quinuclidine portion works as an activator for nucleophiles.…”
mentioning
confidence: 99%
“…Dubey and Chowdhury showed that 1,4-conjugate additions of nitromethane to β-silyl α,β-unsaturated carbonyl compounds catalyzed by bifunctional squaramide catalysts are effective under solvent-free conditions [ 26 ]. Zhai and Du demonstrated that asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins are efficiently catalyzed by cinchona-based thiourea catalysts [ 27 ].…”
mentioning
confidence: 99%